ANALISIS TINGKAT KESEHATAN KOPERASI WANITA DI KOTA MADIUN - Muhamad Agus Sudrajat; Muhammad Tanfidzul Khoiri (Universitas PGRI Madiun, 2018)
This research aime to find level of health of Women’s Cooperative In Madiun City. The Objects of this this research are Women’s Cooperative “Bahtera, Mawar, and Kenanga”. Aspects used to assest healthiness of cooperative are capital aspect, the quality of productive assets, efficiency on management, self-reliance and liquidity growth as well as identity management based on the ordinance of Deputy for supervision of Minister of Cooperative and Small and Middle Enterprises Number: 06/Per/Dep,6/IV/2016. This research use data instruments of financial report 2014-2016 and list of questions referring to managemet aspect of cooperative. The result analysis shows the assesment of Health level of Women’s cooperative in Madiun City in 2014 is quite healthy with average final score of 67.18. in 2015 is on control with average final score of 65.93 in 2014 is on controlwith average final score of 61.10.